Anopheles Mosquito Gene Editing with CRISPR/Cas9 to Prevent Malaria as an Effort to Help Military Peacekeeping Operations - Firmansyah, Hafid Irza; Djatmiko, Christine Bella Putri; Faiza, Yaumi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
Malaria, caused by Plasmodium transmitted by Anopheles mosquitoes, has a significant global impact, especially in endemic areas where military and peacekeeping forces operate. CRISPR/Cas9 gene editing technology provides hope for reducing the spread of this disease. The focus of this research is on genetic modification of Anopheles mosquitoes by evaluating the potential of CRISPR/Cas9 in preventing malaria transmission in military personnel involved in peace operations. The Anopheles study demonstrated success in mediated knockout of the FREP1 gene, resulting in a reduction in the prevalence of Plasmodium infected mosquitoes. The use of CRISPR techniques provided efficient results with positive impacts on genetic modification, but also demonstrated negative impacts on mosquito fitness, including reduced fecundity and slower pre-adult development. Application of CRISPR/Cas9 to A. gambiae mosquitoes showed a reduction in Plasmodium infection intensity, but with impacts such as lower blood feeding propensity, reduced fecundity, and decreased longevity. Ethical implications need to be considered, including impacts on biodiversity and environmental safety. In implementing CRISPR/Cas9, it is necessary to consider public participation and acceptance, as well as capacity building for fair decisions to effectively address malaria.